Beef Cattle Feed Requirements - Kuhl, Gerry L.; Jones, Rodney D. (My University, 1995)
This publication describes the feed requirements for beef cattle for Kansas beef producers.
MF264_1995_10
Keywords: MF264; Livestock; MF